GOLD-TELLURIUM-BISMUTH MINERALIZATION FROM THE ZADERZHNINSKOE DEPOSIT (SOUTH VERKHOYANSK REGION, EAST YAKUTIA) - G.S. Anisimova; L.A. Kondrat′eva (South Urals Federal Research Center of Mineralogy and Geoecology UB RAS, 2016)
The detailed mineralogical studies of the Zaderzninskoe deposit showed diverse mineral composition. Various tellurides (hedleyite), sulfotellurides and sulfosalts of silver, bismuth and lead (minerals of tetradymite group, minerals of lillianite-gustavite series), and native bismuth were identified for the first time, as well as their secondary tellurites and oxides. Native gold of fineness of 750 ‰ is associated with Te-Bi minerals.